Bridging Technology and Entrepreneurship: A Needs Analysis of Appropriate Technology Training for Farmers in Indonesia - Abdullah Basalamah; Muhammad Zainal Altim (Journal of Economic Education and Entrepreneurship Studies, 2026)
This study presents a needs analysis for developing an entrepreneurship-based Appropriate Technology (AT) training model for farmers in Borisallo Village, Parangloe District, Gowa Regency, Indonesia. The study aims to identify farmers' entrepreneurial competencies, technology adoption readiness, and training requirements as the foundation for future training model development. A descriptive qualitative approach supported by quantitative data was employed involving 23 purposively selected farmers. Data were collected through observations, semi-structured interviews, and questionnaires, and analyzed using qualitative thematic analysis, descriptive statistics, and triangulation. The needs analysis revealed substantial gaps in entrepreneurial competencies, particularly in independence, work attitude, risk-taking, and problem-solving, alongside limited experience in using appropriate agricultural technologies. Most farmers had never participated in Appropriate Technology training and continued to rely on traditional farming practices. These findings indicate that farmers require an integrated training program combining technical competencies with entrepreneurship development. The study concludes that the results of this needs analysis provide an empirical foundation for designing an entrepreneurship-based Appropriate Technology training model that supports technology adoption, business development, and sustainable rural economic empowerment.